Seasonal Patterns of Water Cycling in a Deep, Continental Mountain Valley Inferred From Stable Water Vapor Isotopes. Issue 14 (21st July 2018) - Fiorella, Richard P.; Poulsen, Christopher J.; Matheny, Ashley M.
Abstract: The origin of atmospheric moisture is difficult to determine from meteorological measurements alone. Stable water vapor isotopes can be used to trace the atmospheric history of water vapor, and therefore are a powerful tool for understanding water cycle processes across a range of spatial and temporal scales. We present subhourly measurements of summer and winter vapor isotope ratios from a deep mountain valley in northwestern Wyoming. Vapor isotopes are paired with local meteorological measurements, and relationships between local vapor isotopic compositions and large‐scale air transport are explored using atmospheric back trajectories and a Lagrangian moisture source diagnostic. Isotopic compositions vary on diurnal to seasonal timescales, and to first order, track changes in local specific humidity. Local vapor isotopic composition varies with air transport pathway in both seasons, but cannot be uniquely mapped to a source region due to continental recycling of vapor. Diurnal variability in d‐excess is substantial in summer, but not in winter. This seasonal contrast is likely driven by local surface and near‐surface processes including evapotranspiration and boundary layer mixing, which partially overprint the source isotope ratios of the regional source during the summer and casts doubt on the use of d‐excess over continental interiors as a tracer of evaporative conditions over the ocean. Continued monitoring of the isotopic composition of near‐surface vapor in continental settings may help detect changes in regional moisture convergence and the local evapotranspiration flux, as well as assess meso‐to‐regional scale responses to hydrologic variability. Key Points: Stable water vapor isotopes respond to local and remote moisture sources in a continental setting and are best described by mixing models Deuterium excess is a poor tracer of oceanic evaporation conditions in continental interiors as most vapor last evaporated over land Local fluxes impact continental vapor d‐excess all year; regional fluxes also impact winter d‐excess when evapotranspiration is low